NARROW LISTENING: A SUBSET OF EXTENSIVE LISTENING - Anna C-S Chang (TLEMC (Teaching and Learning English in Multicultural Contexts), 2017)
Though narrow listening is not a new approach in developing listening competence, the effectiveness of narrow listening has hardly been reported in the research literature. Narrow listening refers to learners doing a large quantity of listening practice but focusing on the same theme or the same author’s work systematically and consistently for a period of time. When they are familiar with one theme or one author’s work, they move on to the next one. Narrow listening can be seen as another subset of extensive listening because both require learners to receive a massive amount of aural input. In this talk, I will discuss the advantages of using narrow listening in teaching L2 and how to choose materials for implementing narrow listening in an L2 listening course